Patterns of distribution of mollusc fauna associated with Halopteris scoparia (Linnaeus) Sauvageau: a baseline study in the Azores archipelago helps understanding the impact of climate change/invasive species on biodiversity - Ávila, Sérgio P.; Costa, Ana Cristina; Madeira, Patrícia; Brum, João; Prestes, Afonso C. L.; Faria, João; Martins, Gustavo M. (Frontiers in Marine Science, 2024)
We examined the structure of the molluscan communities of the macroalgae Halopteris scoparia in São Miguel Island (Azores, Portugal). This island was chosen because it is the largest and the most populated of the archipelago, with polluted sites which are not common in the Azores. The relationship between the epifaunal assemblages and a set of environmental factors – geographical location (orientation), seawater temperature, depth, algal volume, degree of disturbance, and degree of exposure to the wave action – was investigated using distance-based redundancy analysis and significant variation in the distribution of richness of assemblages was found. Four environmental predictors were common to all the four analyses implemented (richness and assemblage structure using both AIC and BIC): algal volume (that correlates with algal dry weight), seawater temperature, coastal orientation and depth. Finally, the application in the Azores of this methodology favours a sampling program in Spring-Summer (when disturbance seems to be more susceptible to detection), and the use of H. scoparia in the subtidal zone, as the target alga is recommended due to its large covering of rocky shore substrates.